Modularity design of the bamboo plastic fiber forming machine - Thanh Nam Nguyen (EDP Sciences, 2021)
Currently, the research on the application of bamboo wood plastic fibers to 3D printing technology in Vietnam is limited. Almost all studies mainly focus on the application of natural polymers (wood, rubber, coir..) but ignore a rich natural polymer source, popular in Vietnam: bamboo. In addition, the quality of wood plastic fibers applied in 3D printing technology has not responded to the requirements of consumers. The durability of 3D printed parts that is based on wood plastic fibers is not high. Surface gloss of parts after implementation is still rough. During the 3D printing process of wood plastic fibers material, the nozzle is still always clogged due to the blockage of wood pulp. Therefore, the study of technology and equipment for the fabrication of bamboo wood fibers and research on the effect of technological parameters on the finished bamboo-wood-plastic fiber properties is necessary and should be urgently carried out. The paper proposes a new approach to structure modularization of the bamboo wood plastic fiber forming machine by using mostly standard parts, thus improving the quality and reducing the cost of the machine and bamboo wood plastic fiber material for the 3D printer.